Toward an Applied Meaning for Ethics in Business - Robin, D. (Journal of business ethics, 2009)
The field of business ethics has been active for several decades, but it has yet to develop a generally agreed upon applied ethical perspective for the discipline. Academics in business disciplines have developed useful science-based models explaining why business people behave ethically but without a generally accepted definition of ethical behavior. Academics in moral philosophy have attempted to formulate what they believe ethical behavior is, but many seem to ignore or reject the basic mission of business. The purpose of this article is to offer one view of ethics in business that accommodates the mission of business. This purpose is achieved by reviewing the mission of ethics in applied disciplines like business and melding it into the mission of business in capitalistic societies.